A Balanced Scorecard Approach To Measuring Industry Performance - Toong , Khuan Chan; Poh , Tin Hiap (Penerbit Universiti Sains Malaysia, 2012)
Stakeholders of the Malaysian construction industry produced a Construction Industry Master Plan to chart the strategic direction for the industry for a ten-year period between 2006 and 2015. The objectives of this paper were to review the recommendations of the master plan using the Balanced Scorecard approach, to develop a performance management framework for the construction industry and to propose a set of performance measures to allow stakeholders to monitor the progress of the implementation of the master plan in achieving its strategic aims. The Balanced Scorecard approach was used to evaluate the critical success factors, strategic thrusts and recommendations to ensure that the master plan presents a balanced view to enhance the industry's competitive standing. The review revealed that the recommendations generally address all four Balanced Scorecard perspectives but lacked focus on customer relationships in the customer perspective and customer management in the Internal Processes Perspective. Additional recommendations are suggested to address these gaps. A list of key performance measures for the Malaysian construction industry has been selected by linking each strategic thrust with the relevant performance measures.